P PENGEMBANGAN MUFFIN OAT DENGAN PENAMBAHAN PUREE PISANG SEBAGAI MAKANAN SELINGAN UNTUK REMAJA GIZI LEBIH: PENGEMBANGAN MUFFIN OAT DENGAN PENAMBAHAN PUREE PISANG SEBAGAI MAKANAN SELINGAN UNTUK REMAJA GIZI LEBIH - Rosyda Dianah; Dini Juliana (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2025)
Muffins are cup-shaped cakes that are generally consumed as a snack and generally have a high calorie content because of the raw materials used, but muffin can be used as a healthy alternative snack by replacing the main raw material used with oats and also reducing the use of sugar with natural sweeteners which comes from fruit such as bananas which have been made into puree so that they can produce a distinctive taste and aroma. The research method used was pure experimental with data analysis carried out descriptively. The sampling technique used is random sampling using organoleptic tests to see the level of panelists’ liking for the two formulas presented. The results of the analysis from organoleptic tests carried out by 30 panelists with an age range of 18-21 years with the highest percentage being is Formula 1 (F1) with results of >80% of the panelists liked the formula muffin oat with the addition of banana puree. From the analysis,muffin oat with the addition of banana puree was mostrly preferred by panelist and can be used as an alternative snack for teenagers who experience overweight nutritional status. Key words: banana puree, muffin, oats, overweight teenss, snack